Preservation of probiotic strains isolated from kefir by spray drying - Golowczyc, M.A. (2010)
Aims: This work aims to investigate the survival of Lactobacillus kefir CIDCA 8348, Lactobacillus plantarum CIDCA 83114 and Saccharomyces lipolytica CIDCA 812, all isolated from kefir, during spray drying and subsequent storage. Methods and Results: Micro-organisms were grown in De Man, Rogosa, Sharpe (MRS) or yeast medium (YM) medium and harvested in the stationary phase of growth. The thermotolerance in skim milk (D and Z values), the survival of spray drying at different outlet air temperatures and subsequent storage in different conditions during 150 days were studied. The resistance to the heat treatments was higher in Lact. plantarum compared to Lact. kefir and S. lipolytica. The three micro-organisms studied varied considerably in their ability to survive to spray drying processes. Lactobacillus plantarum showed the highest survival rate for all the tested outlet air temperatures and also to the further storage in the dried state. The survival rates of Lact. kefir and S. lipolytica through drying and subsequent storage in the dried state decreased when the drying outlet air temperatures increased. Conclusions: Spray drying is a suitable method to preserve micro-organisms isolated from kefir grains. A high proportion of cells were still viable after 80 days of storage at refrigerated temperatures Significance and Impact of Study: It is the first report about spray-dried probiotic strains isolated from kefir grain and contributes to the knowledge about these micro-organisms for their future application in novel dehydrated products.